Polyolefin elastomer, preparation method and application of polyolefin elastomer in photovoltaic packaging film

By preparing bimodal distributed random or block polymers of ethylene and α-olefins, combined with crosslinking agents, the uneven dispersion and failure problems of photovoltaic adhesive films are solved, and high light transmittance and high efficiency power generation of photovoltaic cells are achieved.

CN120365466APending Publication Date: 2025-07-25WANHUA CHEM GRP CO LTD

Patent Information

Application Number
CN202510599731.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-12
Publication Date
2025-07-25

AI Technical Summary

Technical Problem

The existing photovoltaic adhesive films mainly rely on external addition of inorganic additives, which have problems of uneven dispersion and failure of decomposition over time, and cannot fundamentally improve the light transmittance.

Method used

The random or block polymer composed of ethylene and α-olefin is used to prepare polyolefin elastomers by cationic coordination polymerization to form a bimodal distributed polymer structure, and a photovoltaic encapsulation film is prepared by combining crosslinking agents, aided crosslinking agents and coupling agents.

Benefits of technology

The optimization of the microstructure of the polymer is achieved, the light transmittance of the photovoltaic packaging film is improved, the uneven dispersion and failure of external additives are avoided, and the power generation efficiency of photovoltaic cells is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005396425240000021
    Figure BDA0005396425240000021
  • Figure BDA0005396425240000131
    Figure BDA0005396425240000131
Patent Text Reader

Abstract

The invention provides a polyolefin elastomer for a photovoltaic packaging film as well as a preparation method and application of the polyolefin elastomer, the polyolefin elastomer is a random or block polymer composed of ethylene and alpha-olefin, the molecular weight Mw of the polyolefin elastomer is 40000-100000, the PDI is 2.3-3, the monomer insertion rate is 20-40 wt%, in TGIC trichlorobenzene heating leaching, the elution peak of polyolefin resin is double peaks, and the molecular weight Mw of the polyolefin elastomer is 25000-25000, the PDI of the polyolefin elastomer is 2.3-3, and the monomer insertion rate of the polyolefin elastomer is 20-40 wt%. The temperature difference between two peaks is 35-50 DEG C, the half-peak width of the peak appearing at the position larger than 40 DEG C is 20-28, the elastomer has high light transmittance and additive absorption capacity, and the prepared composition photovoltaic packaging adhesive film has more excellent optical performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a polyolefin elastomer for a photovoltaic encapsulation film, belonging to the technical field of photovoltaic adhesive films. Background Art

[0002] A solar power generation device is a device that converts light energy into electrical energy by using a solar photovoltaic cell module under the action of a P-N junction. A solar cell is a device that directly converts light energy into electrical energy through the photovoltaic effect or a photochemical reaction. When light enters the surface of a solar cell panel, the light first passes through tempered glass, then enters the photovoltaic adhesive film, and then enters the P-N junction region of the cell, forming a photo-generated hole-electron pair. The photo-generated holes flow into the P region, and the photo-generated electrons flow into the N region. Connecting the circuit forms an electric current. The light transmittance determines the power generation efficiency of the photovoltaic cell. Therefore, the light transmittance of the photovoltaic adhesive film is extremely important for the power generation efficiency.

[0003] Most of the previous research on improving the light transmittance of the adhesive film was achieved by adjusting the formula. For example, CN106590471B improved the light transmittance by adding an infrared shielding agent, and CN220550130U achieved the improvement of the light transmittance by adding a light conversion agent. However, the above solutions have the following disadvantages: Whether it is a shielding agent or a light conversion agent, they are all externally added inorganic auxiliaries, and there is a problem of uneven dispersion with the polymer. In addition, the light conversion agent and the like also have the situation that the light conversion agent decomposes or fails over time, and the problem of light transmittance cannot be fundamentally solved. The present invention starts from the perspective of the resin structure of the adhesive film body, changes the polymer microstructure, constructs a crystallization system, and essentially improves the light transmittance of the particles to achieve the improvement of the light transmittance of the adhesive film. Summary of the Invention

[0004] The present invention first prepares a kind of POE particles. The POE structure has good uniformity of insertion rate and uniform crystallization, and can optimize the optical properties of the particles.

[0005] The technical solution adopted by the present invention is as follows:

[0006] On the one hand, the present invention provides a polyolefin elastomer for a photovoltaic encapsulation film. The polyolefin elastomer is a random or block polymer composed of ethylene and α-olefin. In the TGIC trichlorobenzene temperature-rising elution, the elution peak is bimodal, and the temperature difference between the two peaks is 35-50 °C, such as 36 °C, 38 °C, 40 °C, 42 °C, 44 °C, 46 °C, 48 °C; the half-peak width of the peak at a temperature higher than 40 °C is 20-28, such as 21, 22, 23, 24, 25, 26, 27, wherein the peak less than 40 °C reaches the highest at 29-38 °C, and the peak greater than 40 °C reaches the highest at 72-84 °C.

[0007] Furthermore, the polyolefin elastomer has a molecular weight Mw of 40,000 - 100,000, a PDI of 2.3 - 3, and a monomer insertion rate of 20 - 40 wt%.

[0008] Furthermore, the α-olefin is an olefin having 3 - 13 carbon atoms, preferably one or more of propylene, butene, hexene, octene, nonene, and decene.

[0009] Furthermore, the polyolefin elastomer is represented by the structural formula:

[0010]

[0011] wherein n is any integer from 0 to 10, for example: 1, 2, 3, 4, 5, 6, 7, 8, 9.

[0012] In a second aspect, the present invention provides a method for preparing the above polyolefin elastomer.

[0013] Furthermore, the method for preparing the polyolefin elastomer for a photovoltaic encapsulation film comprises the following steps:

[0014] In a cationic coordination polymerization manner, a solvent and an α-olefin are mixed in a certain ratio and then injected into a reaction kettle. At a temperature of 140 - 200 °C, ethylene gas is introduced, and the pressure is 3 - 8 MPa. Then, a main catalyst and a co-catalyst are added to the reaction kettle and stirred for reaction for 10 - 20 minutes. After reacting for 1 - 5 minutes, the introduction of ethylene is stopped, and at the same time, a mixture of ethylene and a chain transfer agent is introduced, maintaining the pressure in the kettle at 3 - 8 MPa, and continuing to react for 10 - 20 minutes to obtain a reactant solution;

[0015] An inactivator is added to the system, and after sufficient reaction, a product is obtained. The product is cooled and dried to obtain a polymer.

[0016] In the preparation method, the solvent is selected from aliphatic hydrocarbon solvents and / or aromatic hydrocarbon solvents; preferably, the aliphatic hydrocarbon solvent is selected from one or more of n-butane, isobutane, n-pentane, cyclopentane, methylcyclopentane, methylene cyclopentane, n-hexane, cyclohexane, methylcyclohexane, ethylcyclohexane, n-heptane, n-octane, n-nonane, or Isopar E; the aromatic hydrocarbon solvent is selected from one or more of benzene, toluene, xylene, monochlorobenzene, dichlorobenzene, and dichlorotoluene;

[0017] The α-olefin is an olefin having 3 - 13 carbon atoms, preferably one or more of propylene, butene, hexene, octene, nonene, and decene;

[0018] The main catalyst is a metallocene catalyst or a post-metallocene catalyst, preferably one or more of dimethylsilyl(N-tert-butylamido)(tetramethylcyclopentadienyl)titanium dichloride, dimethylsilyl(N-tert-butylamido)(tetramethylcyclopentadienyl)dimethyltitanium, dimethylsilyl(N-tert-butylamido)(fluorenyl)titanium dichloride, (pentamethylcyclopentadienyl)trimethoxytitanium, diphenylmethylene(cyclopentadienyl)(9-fluorenyl)zirconium dichloride, dimethyldimethylsilylbis(2-methyl-4-phenyl-1-indenyl)zirconium dichloride, meso-dimethyldisilylbis(1-indenyl)zirconium dichloride, (bis(methylcyclopentadienyl)zirconium dichloride), (bis(1,3-dimethylcyclopentadienyl)zirconium dichloride, (cyclopentadienyl)(1,2-dimethoxyethane)zirconium trichloride, diphenylsilyl(cyclopentadienyl)(9-fluorenyl)zirconium dichloride, rac-dimethyldisilylbis(2-methyl-1-indenyl)zirconium dichloride, diphenylmethylenecyclopentadiene(2,7-di-tert-butyl-fluorenyl)zirconium dichloride, di-p-tolylmethylenecyclopentadiene(2,7-di-tert-butyl-fluorenyl)zirconium dichloride, dimethylbis(propylcyclopentadienyl)hafnium, bis(n-butylcyclopentadienyl)hafnium dichloride, dimethylsilylbis(2-methyl-4-phenylindenylidene)zirconium dichloride; the addition amount of the main catalyst can be confirmed by those skilled in the art according to the catalyst activity and the weight of the target product. Generally, based on the weight of the polymer, the addition amount of the main catalyst is 0.1-10 ppm; for example, 1 ppm, 2 ppm, 3 ppm, 4 ppm, 5 ppm, 6 ppm, 7 ppm, 8 ppm, 9 ppm.

[0019] The cocatalyst is a composition of one or more of aluminoxane, alkylaluminum compound, and alkylaluminum chloride, or a composition of one or more of aluminoxane, alkylaluminum compound, and alkylaluminum chloride and one or more organoboron compounds.

[0020] Preferably, the aluminoxane is selected from methylaluminoxane (MAO), modified methylaluminoxane (MMAO); the alkylaluminum compound is selected from triethylaluminum, triisobutylaluminum, trioctylaluminum, etc.; the alkylaluminum chloride is selected from chloroethylaluminum, sesquialethylaluminum, dichloroethylaluminum, etc.; the organoboron compound is selected from trityltetrakis(pentafluorophenyl)borate, tris(pentafluorophenyl)boron, N,N-dimethylaniliniumtetrakis(pentafluorophenyl)borate, bis(octadecyl)methyltertiaryammoniumtetrakis(pentafluorophenyl)borate, bis(hydrogenated tallow)methyltertiaryammoniumtetrakis(pentafluorophenyl)borate.

[0021] The molar ratio of aluminum to the central metal M of the cocatalyst is Al / M = 1–10000, preferably 1-4000; the molar ratio of boron to the central metal M in the organoboron compound is B / M = 0-10, preferably 0-8, for example, 1, 2, 3, 4, 5, 6, 7.

[0022] The chain transfer agent is a mixture of ethylene and hydrogen, and the two maintain the pressure in the reactor at 3 - 8 MPa. The mixing ratio is 1 - 10:10 - 1, such as 1:1, 1:2, 1:3, 1:4, 1:5, 1:6, 1:7, 1:8, 1:9, 1:10, 2:1, 2:3, 2:5, 2:7, 2:9, 3:1, 3:2, 3:4, 3:5, 3:7, 3:8, 3:10, 4:1, 4:3, 4:5, 4:7, 4:9, 5:1, 5:2, 5:3, 5:4, 5:6, 5:8, 6:1, 6:5, 7:1, 7:2, 7:3, 7:4, 7:5, 7:6, 8:1, 8:3, 8:5, 8:7, 9:1, 9:2, 9:4, 9:5, 9:7, 9:8.

[0023] The inactivator is a mixture of inactivator A and inactivator B. Preferably, the mixing ratio of the two is 1:10 - 3:1; for example, 1:9, 1:8, 1:7, 1:6, 1:5, 1:4, 1:3, 1:2, 1:1, 2:1. Among them, inactivator A is water and inactivator B is isopropanolamine. The dosage of the inactivator is 2000 - 10000 ppm, such as 3000 ppm, 4000 ppm, 5000 ppm, 6000 ppm, 7000 ppm, 8000 ppm, 9000 ppm.

[0024] In another aspect, the present invention provides the application of the above polyolefin elastomer in the preparation of a photovoltaic encapsulation film.

[0025] Furthermore, the photovoltaic encapsulation film comprises a polyolefin elastomer, a crosslinking agent, a co - crosslinking agent, and a coupling agent;

[0026] In a specific embodiment, the dosages of each component are as follows:

[0027] Polyolefin elastomer: 100 parts by weight,

[0028] Crosslinking agent: 0.1 - 5 parts by weight, preferably 0.5 - 2 parts by weight,

[0029] Co - crosslinking agent: 0.1 - 5 parts by weight, preferably 0.1 - 2 parts by weight,

[0030] Coupling agent: 0.1 - 3 parts by weight, preferably 0.1 - 1 part by weight;

[0031] Further, the crosslinking agent is a peroxide crosslinking agent, including but not limited to one or more of the following: isopropyl t-butyl peroxycarbonate, 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexane, 2-ethylhexyl t-butyl peroxycarbonate, 1,1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane, 1,1-bis(tert-amylperoxy)-3,3,5-trimethylcyclohexane, 1,1-bis(tert-amylperoxy)-3,3,5-trimethylcyclohexane, 1,1-bis(tert-amylperoxy)cyclohexane, 1,1-bis(tert-butylperoxy)cyclohexane, 2,2-bis(tert-butylperoxy)butane, tert-butyl 2-ethylhexyl peroxycarbonate, tert-amyl (2-ethylhexyl) peroxycarbonate, tert-butyl 3,3,5-trimethylhexanoate peroxide;

[0032] Further, the co-crosslinking agent is one or more of multi-functional acrylate substances, including but not limited to: trimethylolpropane triacrylate, trimethylolpropane trimethacrylate, pentaerythritol triacrylate, triallyl isocyanurate, ethoxylated trimethylolpropane triacrylate, propoxylated trimethylolpropane triacrylate, ethoxylated glycerol triacrylate, propoxylated glycerol triacrylate, pentaerythritol tetraacrylate, ethoxylated pentaerythritol tetraacrylate, trimethylolpropane tetraacrylate, bis-trimethylolpropane tetraacrylate, bis-trimethylolpropane tetramethacrylate, propoxylated pentaerythritol tetraacrylate, tricyclodecane dimethanol diacrylate, propoxylated neopentyl glycol diacrylate, ethoxylated bisphenol A diacrylate, ethoxylated bisphenol A dimethacrylate, 2-butyl-2-ethyl-1,3-propanediol diacrylate, diethylene glycol dimethacrylate, triethylene glycol dimethacrylate, polyethylene glycol dimethacrylate;

[0033] Further, the coupling agent is a silane coupling agent, including but not limited to one or more of the following: γ-chloropropylmethoxysilane, dimethylethenyloxyethoxysilane, vinyltris(β-methoxyethoxy)silane, γ-methacryloxypropyltrimethoxysilane, vinyltriacetoxysilane, γ-glycidoxypropyltrimethoxysilane, 3-(trimethoxysilyl)propyl-2-methyl-2-acrylate, anilinomethyltriethoxysilane, octyltrimethoxysilane;

[0034] Further, the photovoltaic encapsulation film can be prepared by conventional methods in the art, for example, including the following steps: high-temperature premixing of raw materials, melt extrusion, casting into a film, cooling, slitting, and winding.

[0035] The beneficial effects of the present invention are as follows:

[0036] The present invention starts from the resin structure of the film substrate to obtain a polymer with a double peak in the elution peak during the temperature rise elution of TGIC trichlorobenzene, the temperature difference between the two peaks is 35 - 50 °C, and the half-peak width of the peak at a temperature greater than 40 °C is 20 - 28. The crystal grains of this polymer in the TGIC crystallization column are relatively uniform, so that the light transmittance of the product is relatively high. When preparing a film with these particles, there is no need to upgrade the film formula, which can fundamentally improve the light transmittance of the photovoltaic film. Detailed implementation manners

[0037] The following further illustrates the present invention through specific examples. The examples described in the present invention are only for the purpose of illustrating the present invention and do not limit the scope of the present invention.

[0038] In this application, "parts" and "%" are by weight, unless otherwise specified.

[0039] Main materials:

[0040] Ethylene-octene copolymer A (Mw is 64700, PDI is 2.4, density is 0.871 g / cm3, octene content is 33.6 wt%, temperature difference between the two peaks is 47.8 °C, half-peak width of the peak at a temperature greater than 40 °C is 20.1, self-made)

[0041] Ethylene-octene copolymer B (Mw is 75200, PDI is 2.4, density is 0.872 g / cm3, octene content is 37 wt%, temperature difference between the two peaks is 49.1 °C, half-peak width of the peak at a temperature greater than 40 °C is 23.8, self-made)

[0042] Ethylene-butene copolymer C (Mw is 69700, PDI is 2.31, density is 0.874 g / cm3, butene content is 24 wt%, temperature difference between the two peaks is 42.7 °C, half-peak width of the peak at a temperature greater than 40 °C is 22.6, self-made)

[0043] Ethylene-hexene copolymer D (Mw is 42700, PDI is 2.5, density is 0.875 g / cm3, hexene content is 30 wt%, temperature difference between the two peaks is 37.2 °C, half-peak width of the peak at a temperature greater than 40 °C is 27.9, self-made)

[0044] Ethylene-octene copolymer E (Mw is 98000, PDI is 2.5, density is 0.873 g / cm3, octene content is 32.5 wt%, temperature difference between the two peaks is 49.8 °C, half-peak width of the peak at a temperature greater than 40 °C is 26.1, self-made)

[0045] Ethylene-hexene copolymer F (Mw is 71000, PDI is 2.3, density is 0.873 g / cm3, hexene content is 35 wt%, temperature difference between the two peaks is 57.2 °C, half-peak width of the peak at a temperature greater than 40 °C is 34, self-made)

[0046] Ethylene / 1-octene copolymer G (Mw is 69,000, PDI is 2.5, density is 0.873 g / cm3, octene content is 35 wt%, temperature difference between two peaks is 40.9 °C, half-peak width of the peak at greater than 40 °C is 15, self-made).

[0047] Methylaluminoxane, from AkzoNobel, 10% toluene solution;

[0048] Modified methylaluminoxane mmao, 7% aluminum solution, from Nouryon

[0049] Dimethylsilylbis(2-methyl-4-phenylindenyl)zirconium dichloride, from Yaodexin Chemical Industry;

[0050] Di-p-tolylmethylene cyclopentadienyl(2,7-di-tert-butyl-fluorenyl)zirconium dichloride, from Yanfeng Technology, Dimethylsilyl(N-tert-butylamino)(tetramethylcyclopentadienyl)dimethyltitanium, from Jiangsu Xinnuoke Catalyst Co., Ltd., Dimethylbis(propylcyclopentadienyl)hafnium, from Yanfeng Technology, Diphenylmethylene cyclopentadienyl(2,7-di-tert-butyl-fluorenyl)zirconium dichloride, from Yaodexin Chemical Industry,

[0051] Dimethylsilyl(tert-butylamino)tetramethylcyclopentadienyldimethyltitanium, from Xinnuoke.

[0052] Testing instruments:

[0053] Melt index tester: Zwick Mflow, testing standard ASTM D1238

[0054] The extruder is a single-screw extruder (L / D = 35), screw diameter is 30 mm,

[0055] Molecular weight and insertion rate tester: Polymer Char, GPC-IR. This instrument has three MIXED chromatographic columns in series inside, with a size of 300 * 7.5 mm; it is equipped with three detectors: infrared, viscosity, and laser. The commonly used IR5 MCT polyolefin special infrared detector is used for detection; the sample is automatically injected with 8 ml of trichlorobenzene solvent in the high-temperature zone (160 °C) of the instrument's automatic sampler, shaken and dissolved for one hour, and then 200 μL is extracted for testing. The temperature of the infrared detector is 150 °C. The molecular weight standard sample used is PS, and the monomer calibration line is established using a series of POEs with different monomer content gradients.

[0056] Soluble matter analysis: Polymer Char, TGIC, solvent trichlorobenzene. TGIC realizes the separation and characterization of different components of polyolefins by temperature rising elution. The sample is dissolved in trichlorobenzene at 165°C and passed through the TGIC chromatographic column. The temperature is programmed to drop to 40°C (20°C / min). Some polyolefin structures adhere to the chromatographic column due to adsorption and crystallization with the graphite column and are rinsed at a flow rate of 0.5 ml / min. The soluble part is flushed to the detector IR5 for detection. The temperature is raised by elution at a rate of 2°C / min to 165°C, and the molecules attached to the column are eluted successively according to their crystallization ability differences and the number of short branches.

[0057] Half-peak width: In the elution curve above 40°C, the temperature difference of the abscissa corresponding to half of the highest peak value (dw / dt).

[0058] The transmittance is tested according to the spectrophotometer method of GB / T 2410-2008

[0059] Preparation Example 1:

[0060] Preparation of ethylene-octene copolymer A: By cationic metallocene coordination polymerization, 2.8 kg of octene is added to 4.2 kg of n-butane solvent, and after forming a solution, it is added to the reaction kettle. The temperature is raised to 150°C, and ethylene gas is introduced to control the pressure in the kettle to be 3 MPa. 1 mg of the main catalyst dimethylsilyl bis(2-methyl-4-phenylindenyl) zirconium dichloride is added to the reaction kettle and the co-catalyst (methylaluminoxane toluene solution with an Al concentration of 1.5 mol / L) is added according to Al / Zr = 500. After stirring and reacting for 5 minutes, the ethylene valve is closed, and a mixture of ethylene and hydrogen is introduced with a mass ratio of ethylene to hydrogen of 6:1. The pressure in the kettle is continuously maintained at 3 MPa, and the reaction is continued for another 15 minutes to obtain the reactant solution;

[0061] Water and isopropanolamine are mixed in a mass ratio of 5:1. After the mixture with a total mass of 34.9 g reacts fully with the reactant solution, the obtained product is cooled, filtered and dried to obtain ethylene-octene copolymer A. Mw is 64700, PDI is 2.4, and the density is 0.871 g / cm 3 , the octene content is 33.6 wt%, the temperature difference between the two peaks is 47.8°C, the half-peak width of the peak above 40°C is 20.1, the peak temperature below 40°C is 32.4, and the peak temperature above 40°C is 80.2°C

[0062] Preparation of ethylene-octene copolymer B: cationic metallocene coordination polymerization was adopted, 4.08 kg of octene was added to 5.88 kg of Isopar E, and the solution was added to the reactor, the temperature was raised to 145°C, ethylene gas was introduced, and the pressure in the reactor was controlled to be 5 MPa. 4.88 mg of the main catalyst di-p-toluene methylene cyclopentadiene (2,7-di-tert-butyl-fluorenyl) zirconium dichloride was added to the reactor, and a co-catalyst (methylaluminoxane toluene solution with an Al concentration of 1.5 mol / L) was added according to Al / Zr=2100. After stirring and reacting for 3 minutes, the ethylene valve was closed, and a mixture of ethylene and hydrogen was introduced, with a mass ratio of ethylene to hydrogen of 8:1. The pressure in the reactor was maintained at 5 MPa, and the reaction was continued for 14 minutes to obtain a reactant solution;

[0063] Water and isopropanolamine were mixed in a mass ratio of 9:1, and the total mass of the mixed solution was 10.5 g. After the mixture was mixed with the reactant solution and fully reacted, the obtained product was cooled to obtain a solid precipitate, which was filtered and dried to obtain ethylene-octene copolymer B. Mw was 75200, PDI was 2.4, and density was 0.872 g / cm 3 , octene insertion rate 37wt%, temperature difference between the two peaks 49.1℃, half peak width of the peak above 40℃ is 23.8. The peak temperature below 40℃ is 32, and the peak temperature above 40℃ is 81.1℃

[0064] Preparation of ethylene-butene copolymer C: cationic metallocene coordination polymerization was adopted, 1.9 kg of butene was added to 5.7 kg of Isopar E, and the solution was added to the reactor, the temperature was raised to 155°C, ethylene gas was introduced, and the pressure in the reactor was controlled to be 3.8 MPa. 16.4 mg of the main catalyst dimethylsilyl (N-tert-butylamino) (tetramethylcyclopentadienyl) dimethyltitanium was added to the reactor, and a co-catalyst (7% Al Isopar E modified methylaluminoxane solution) was added according to Al / Ti=3000. After stirring and reacting for 4 minutes, the ethylene valve was closed, and a mixture of ethylene and hydrogen was introduced, with a mass ratio of ethylene to hydrogen of 2:1. The pressure in the reactor was maintained at 3.8 MPa, and the reaction was continued for 12 minutes to obtain a reactant solution;

[0065] After water and isopropanolamine were mixed at a mass ratio of 10:3, the total mass of the mixed solution of 39.15g was fully reacted with the reactant solution, and the obtained product was cooled, filtered and dried to obtain ethylene-butene copolymer C. Mw was 69700, PDI was 2.31, density was 0.874g / cm3, butene insertion rate was 24wt%, the temperature difference between the two peaks was 42.7℃, the half-peak width of the peak above 40℃ was 22.6, the peak temperature below 40℃ was 33.5, and the peak temperature above 40℃ was 76.2℃

[0066] Preparation of ethylene-hexene copolymer D: By using cationic metallocene coordination polymerization method, 3.3 kg of hexene was added to 8.9 kg of Isopar E solvent. After forming a solution, it was added to the reaction kettle. The temperature was raised to 140 °C, and ethylene gas was introduced, controlling the pressure in the kettle to be 4 MPa. 23.2 mg of the main catalyst dimethylbis(propylcyclopentadienyl)hafnium was added to the reaction kettle, and the co-catalyst (methylaluminoxane toluene solution with Al concentration of 1.5 mol / L) was added according to Al / Hf = 8000. After stirring and reacting for 1 minute, the ethylene valve was closed, and a mixture of ethylene and hydrogen was introduced, with the mass ratio of ethylene to hydrogen being 6:1. Keeping the pressure in the kettle at 4 MPa, the reaction continued for another 16 minutes to obtain the reactant solution;

[0067] After mixing water and isopropanolamine in a mass ratio of 1:1, a total of 15.6 g of the mixed solution was fully reacted with the reactant solution. The obtained product was cooled, filtered and dried to obtain ethylene-hexene copolymer D. Mw was 42700, PDI was 2.5, density was 0.875 g / cm3, hexene content was 30 wt%, the temperature difference between the two peaks was 37.2 °C, the half-peak width of the peak at above 40 °C was 27.9, the peak temperature below 40 °C was 36.8 °C, and the peak temperature above 40 °C was 74 °C.

[0068] Preparation of ethylene-octene copolymer E: By using cationic metallocene coordination polymerization method, 2.45 kg of octene was added to 5.68 kg of Isopar E solvent. After forming a solution, it was added to the reaction kettle. The temperature was raised to 150 °C, and ethylene gas was introduced, controlling the pressure in the kettle to be 3.5 MPa. 16.4 mg of the main catalyst diphenylmethylene cyclopentadiene(2,7-di-tert-butyl-fluorenyl)zirconium dichloride was added to the reaction kettle, and the co-catalyst (7% Al Isopar E modified methylaluminoxane solution) was added according to Al / Zr = 1000. After starting stirring and reacting for 5 minutes, the valve was closed, and a mixture of ethylene and hydrogen was introduced, with the mass ratio of ethylene to hydrogen being 10:1. Keeping the pressure in the kettle at 3.5 MPa, the reaction continued for another 15 minutes to obtain the reactant solution;

[0069] After mixing water and isopropanolamine in a mass ratio of 9:1, a total of 5.31 g of the mixed solution was fully reacted with the reactant solution. The obtained product was cooled, filtered and dried to obtain ethylene-octene copolymer E. Mw was 98000, PDI was 2.5, density was 0.873 g / cm3, octene content was 32.5 wt%, the temperature difference between the two peaks was 49.8 °C, the half-peak width of the peak at above 40 °C was 26.1, the peak temperature below 40 °C was 32.7 °C, and the peak temperature above 40 °C was 82.5 °C.

[0070] Preparation of ethylene-hexene copolymer F: By means of cationic metallocene coordination polymerization, 4.44 kg of hexene was added to 7.5 kg of n-butane solvent. After forming a solution, it was added to the reaction kettle. The temperature was raised to 155 °C, and ethylene gas was introduced, controlling the pressure in the kettle to be 4.4 MPa. 22.5 mg of the main catalyst dimethylsilyl(tert-butylamino)tetramethylcyclopentadienyl dimethyltitanium was added to the reaction kettle, and the cocatalyst (10 wt% methylaluminoxane toluene solution with an Al concentration of 1.5 mol / L) was added according to Al / Zr = 600. Stir and react for 16 min to obtain the reactant solution;

[0071] After reacting 3.5 g of water with the reaction solution, the obtained product was cooled, filtered and dried to obtain ethylene-hexene copolymer F. Mw was 71000, PDI was 2.3, the density was 0.873 g / cm3, the hexene content was 35 wt%, the temperature difference between the two peaks was 57.2 °C, the half-peak width of the peak at above 40 °C was 34, the peak temperature below 40 °C was 28.5 °C, and the peak temperature above 40 °C was 85.7 °C.

[0072] Preparation of ethylene-octene copolymer G: An ethylene / 1-octene copolymer was prepared by performing the following continuous polymerization process using a 2.5 L polymerization reactor equipped with a stirrer:

[0073] The solvent, 8.5 kg / h of n-hexane, 1.5 kg / h of ethylene, and 0.9 kg / h of 1-octene were cooled to -40 °C through a primary heat exchanger and then injected into the reactor. The stirrer prepared the reactants and then placed them at the bottom (bottom surface) of the polymerization reactor. In addition, triisobutylaluminum as a scavenger was introduced into the bottom of the polymerization reactor at a flow rate of 23 mmol / hr through a pipeline separate from the pipeline introducing the reactants.

[0074] First, at -30 °C, methyllithium (1.63 g, 3.55 mmol, 1.6 M diethyl ether solution) was added dropwise to a diethyl ether solution (10 mL) dissolving compound (1) (0.58 g, 1.79 mmol). The obtained solution was stirred overnight at room temperature, then cooled to -30 °C, and 0.37 g (1.79 mmol) of Ti(NMe2)2Cl2 was added at once. The obtained solution was stirred for 3 hours, and then all the solvents were removed using a vacuum pump. As a result, a red solid compound (0.59 g, yield 75%) was obtained.

[0075] The existence of two stereoisomers in a ratio of 1:0.8 was confirmed by 1H NMR spectroscopy. The obtained transition metal compound was added to the bottom of the polymerization reactor at a flow rate of 0.114 mmol / hr, and the cocatalyst compound N,N-dimethylanilinium tetrakis(pentafluorophenyl)borate was added to the bottom of the polymerization reactor at a flow rate of 0.3 mmol / hr.

[0076] The polymerization reaction was carried out by setting the pressure in the polymerization reactor to 90 bar.

[0077] After passing through the polymerization reactor, the obtained product was passed through a first recovery device at 40 °C and 5 bar to recover the solvent, and then through a second recovery section at 30 °C and 1 bar to recover the remaining n-hexane and unreacted ethylene.

[0078] The remaining ethylene / 1-octene copolymer was recovered using a separation column, and the ethylene / 1-octene copolymer was solidified using a pelletizer to obtain Polymer G. Mw was 69000, PDI was 2.5, density was 0.873 g / cm3, octene content was 35 wt%, the temperature difference between the two peaks was 40.9 °C, the half-peak width of the peak at above 40 °C was 15, the peak temperature below 40 °C was 39.1 °C, and the peak temperature above 40 °C was 80 °C.

[0079] Examples and Comparative Examples:

[0080] Example 1:

[0081] 9 g of tert-butyl peroxy-2-ethylhexyl carbonate, 6 g of triallyl isocyanurate, 2 g of γ-methacryloxypropyltrimethoxysilane, and 1 g of γ-(2,3-epoxypropoxy)propyltrimethoxysilane were added to 1000 g of ethylene-octene copolymer A. The above raw materials were heated to 50 °C and mixed evenly. The parameters of the extruder were adjusted. The temperatures from the feeding port to the die head were 80 °C, 90 °C, 90 °C, 90 °C, 90 °C, 95 °C, 95 °C, 95 °C. The screw speed was 45 rpm, the traction speed was 0.7 rpm, and the winding speed was 1.3 rpm. Through the processes of extrusion, casting into a film, cooling and slitting, and winding, an encapsulation film for photovoltaic modules was prepared, and the film thickness was 0.6 mm.

[0082] Example 2

[0083] Add 6 g of 1,1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane, 2 g of tert-amyl peroxy(2-ethylhexyl) carbonate, 4 g of trimethylolpropane triacrylate, 2 g of γ-methacryloxypropyltrimethoxysilane, and 1 g of γ-(2,3-epoxypropoxy)propyltrimethoxysilane to 1000 g of ethylene-octene copolymer B. Heat the above raw materials to 50 °C and mix evenly. Adjust the parameters of the extruder. The temperatures from the feeding port to the die head are 80 °C, 90 °C, 90 °C, 90 °C, 90 °C, 95 °C, 95 °C, 95 °C. The screw speed is 45 rpm, the traction speed is 0.7 rpm, and the winding speed is 1.3 rpm. Through the processes of extrusion, casting into film, cooling, slitting, and winding, a packaging adhesive film for photovoltaic modules is prepared, and the film thickness is 0.6 mm.

[0084] Example 3

[0085] Add 20 g of tert-butyl peroxy(2-ethylhexyl) carbonate, 7 g of triallyl isocyanurate, and 8 g of dimethylethenyl ethoxysilane to 1000 g of ethylene-butene copolymer C. Heat the above raw materials to 50 °C and mix evenly. Adjust the parameters of the extruder. The temperatures from the feeding port to the die head are 80 °C, 90 °C, 90 °C, 90 °C, 90 °C, 95 °C, 95 °C, 95 °C. The screw speed is 45 rpm, the traction speed is 0.7 rpm, and the winding speed is 1.3 rpm. Through the processes of extrusion, casting into film, cooling, slitting, and winding, a packaging adhesive film for photovoltaic modules is prepared, and the film thickness is 0.6 mm.

[0086] Example 4

[0087] Add 15 g of 2,2-bis(tert-butylperoxy)butane, 10 g of triallyl isocyanurate, and 10 g of γ-methacryloxypropyltrimethoxysilane to 1000 g of ethylene-hexene copolymer D. Heat the above raw materials to 50 °C and mix evenly. Adjust the parameters of the extruder. The temperatures from the feeding port to the die head are 80 °C, 90 °C, 90 °C, 90 °C, 90 °C, 95 °C, 95 °C, 95 °C. The screw speed is 45 rpm, the traction speed is 0.7 rpm, and the winding speed is 1.3 rpm. Through the processes of extrusion, casting into film, cooling, slitting, and winding, a packaging adhesive film for photovoltaic modules is prepared, and the film thickness is 0.6 mm.

[0088] Example 5

[0089] Add 10 g of tert-butyl peroxy-2-ethylhexyl carbonate, 8 g of triallyl isocyanurate, 2 g of octyltrimethoxysilane, and 1 g of γ-(2,3-epoxypropoxy)propyltrimethoxysilane to 1000 g of ethylene-octene copolymer E. Heat the above raw materials to 50°C and mix them evenly. Adjust the parameters of the extruder. The temperatures from the feed port to the die head are 80°C, 90°C, 90°C, 90°C, 90°C, 95°C, 95°C, 95°C, the screw speed is 45 rpm, the traction speed is 0.7 rpm, and the winding speed is 1.3 rpm. Through the processes of extrusion, casting into film, cooling and slitting, and winding, a packaging film for photovoltaic modules is prepared, and the film thickness is 0.6 mm.

[0090] Comparative Example 1

[0091] Add 9 g of tert-butyl peroxy-2-ethylhexyl carbonate, 6 g of triallyl isocyanurate, 2 g of γ-methacryloxypropyltrimethoxysilane, and 1 g of γ-(2,3-epoxypropoxy)propyltrimethoxysilane to 1000 g of ethylene-hexene copolymer F. Heat the above raw materials to 50°C and mix them evenly. Adjust the parameters of the extruder. The temperatures from the feed port to the die head are 80°C, 90°C, 90°C, 90°C, 90°C, 95°C, 95°C, 95°C, the screw speed is 45 rpm, the traction speed is 0.7 rpm, and the winding speed is 1.3 rpm. Through the processes of extrusion, casting into film, cooling and slitting, and winding, a packaging film for photovoltaic modules is prepared, and the film thickness is 0.6 mm.

[0092] Comparative Example 2

[0093] Add 9 g of tert-butyl peroxy-2-ethylhexyl carbonate, 6 g of triallyl isocyanurate, 2 g of γ-methacryloxypropyltrimethoxysilane, and 1 g of γ-(2,3-epoxypropoxy)propyltrimethoxysilane to 1000 g of ethylene-octene copolymer G. Heat the above raw materials to 50°C and mix them evenly. Adjust the parameters of the extruder. The temperatures from the feed port to the die head are 80°C, 90°C, 90°C, 90°C, 90°C, 95°C, 95°C, 95°C, the screw speed is 45 rpm, the traction speed is 0.7 rpm, and the winding speed is 1.3 rpm. Through the processes of extrusion, casting into film, cooling and slitting, and winding, a packaging film for photovoltaic modules is prepared, and the film thickness is 0.6 mm.

[0094] Use the packaging films prepared in the above examples and comparative examples to prepare photovoltaic modules, and test their light transmittance and PID performance. The test results are shown in the following table;

[0095] Among them, the test method is as follows:

[0096] Light transmittance test: Conduct the test according to the spectrophotometer method of GB / T 2410-2008, and calculate the average light transmittance values in the wavelength ranges of 290 nm to 380 nm and 380 nm to 1100 nm respectively.

[0097] Test results of examples and comparative examples:

[0098]

[0099] From the comparison of the performance test data of the examples and comparative examples described in the above table, it can be seen that:

[0100] The polyolefin elastomer and its composition for photovoltaic encapsulation film provided by the present invention control the uniformity of monomer insertion during the synthesis of the matrix resin, improve the light transmittance of the matrix resin itself, and the made photovoltaic film does not need to add additional formulations, making its optical properties very excellent.

[0101] The above are only the preferred embodiments of the present invention. It should be noted that for those of ordinary skill in the art, without departing from the method of the present invention, several improvements and supplements can be made, and these improvements and supplements should also be regarded as the protection scope of the present invention.

Claims

1. A polyolefin elastomer, characterized in that, The polyolefin elastomer is a random or block polymer composed of ethylene and α-olefin. In the temperature rising elution of TGIC trichlorobenzene, the elution peak is bimodal, and the temperature difference between the two peaks is 35-50 °C; the half-peak width of the peak at a temperature higher than 40 °C is 20-28.

2. The polyolefin elastomer according to claim 1, wherein The molecular weight Mw of the polyolefin elastomer is 40,000-100,000, the PDI is 2.3-3, and the monomer insertion rate is 20-40 wt%; and / or, the α-olefin is an olefin with 3-13 carbon atoms, preferably one or more of propylene, butene, hexene, octene, nonene and decene.

3. The method for preparing a polyolefin elastomer according to claim 1 or 2, characterized in that, Comprising the following steps: By means of cationic coordination polymerization, the solvent and α-olefin are mixed in proportion and then injected into the reaction kettle. At a temperature of 140-200 °C, ethylene gas is introduced, and the pressure is 3-8 MPa. Then the main catalyst and the co-catalyst are added to the reaction kettle and stirred for reaction for 10-20 minutes. After reacting for 1-5 minutes, the introduction of ethylene is stopped, and at the same time, a mixture of ethylene and chain transfer agent is introduced, keeping the pressure in the kettle at 3-8 MPa, and continuing to react for 10-20 minutes to obtain a reactant solution; An inactivator is added to the system, and after sufficient reaction, a product is obtained. The product is cooled and dried to obtain a polymer.

4. The preparation method according to claim 3, characterized in that, The main catalyst is a metallocene catalyst or a post-metallocene catalyst, preferably one or more of dimethylsilyl(N-tert-butylamido)(tetramethylcyclopentadienyl)titanium dichloride, dimethylsilyl(N-tert-butylamido)(tetramethylcyclopentadienyl)dimethyltitanium, dimethylsilyl(N-tert-butylamido)(fluorenyl)titanium dichloride, (pentamethylcyclopentadienyl)trimethoxytitanium, dibenzylidene(cyclopentadienyl)(9-fluorenyl)zirconium dichloride, dimethyldimethylsilylbis(2-methyl-4-phenyl-1-indenyl)zirconium dichloride, meso-dimethyldisilylbis(1-indenyl)zirconium dichloride, (bis(methylcyclopentadienyl)zirconium dichloride), (bis(1,3-dimethylcyclopentadienyl)zirconium dichloride, (cyclopentadienyl)(1,2-dimethoxyethane)zirconium trichloride, diphenylsilyl(cyclopentadienyl)(9-fluorenyl)zirconium dichloride, racemic-dimethyldisilylbis(2-methyl-1-indenyl)zirconium dichloride, dibenzylidenecyclopentadiene(2,7-di-tert-butyl-fluorenyl)zirconium dichloride, di-p-tolylidenecyclopentadiene(2,7-di-tert-butyl-fluorenyl)zirconium dichloride, dimethylbis(propylcyclopentadienyl)hafnium, bis(n-butylcyclopentadienyl)hafnium dichloride, dimethylsilylbis(2-methyl-4-phenylindenylidene)zirconium dichloride; and / or, the addition amount of the main catalyst is 0.1-10 ppm.

5. The preparation method according to claim 3 or 4, characterized in that, The cocatalyst is a composition of one or more of aluminoxane, alkylaluminum compounds, and alkylaluminum chlorides, or a composition of one or more of aluminoxane, alkylaluminum compounds, and alkylaluminum chlorides and one or more organoboron compounds; preferably, the aluminoxane is selected from methylaluminoxane (MAO) and modified methylaluminoxane (MMAO); the alkylaluminum compounds are selected from triethylaluminum, triisobutylaluminum, trioctylaluminum, etc.; the alkylaluminum chlorides are selected from chloroethylaluminum, sesquialethylaluminum, dichloroethylaluminum, etc.; the organoboron compounds are selected from trityltetrakis(pentafluorophenyl)borate, tris(pentafluorophenyl)boron, N,N-dimethylanilinium tetrakis(pentafluorophenyl)borate, bis(octadecyl)methylamine tetrakis(pentafluorophenyl)borate, and bis(hydrogenated tallow)methylamine tetrakis(pentafluorophenyl)borate.

6. The preparation method according to any one of claims 3-5, characterized in that, The molar ratio of aluminum to the central metal M of the catalyst in the cocatalyst, Al / M, is 1–10,000, preferably 1-4,000; the molar ratio of boron to the central metal M of the catalyst in the organoboron compound, B / M, is 0-10, preferably 0-8; and / or, the chain transfer agent is a mixture of ethylene and hydrogen, and the two maintain the pressure in the reactor at 3-8 Mpa, and the mixing ratio is 1-10:10-1.

7. Application of the polyolefin elastomer according to any one of claims 1-2 or the polyolefin elastomer prepared by the preparation method according to any one of claims 3-6 in a photovoltaic encapsulation film.

8. The application according to claim 7, wherein The photovoltaic encapsulation film described above contains a polyolefin elastomer, a crosslinking agent, a co-crosslinking agent, and a coupling agent.

9. The application according to claim 7 or 8, characterized in that, The dosages of the components of the photovoltaic encapsulation film described above are as follows: Polyolefin elastomer: 100 parts by weight, Crosslinking agent: 0.1-5 parts by weight, preferably 0.5-2 parts by weight, Co-crosslinking agent: 0.1-5 parts by weight, preferably 0.1-2 parts by weight, Coupling agent: 0.1-3 parts by weight, preferably 0.1-1 part by weight.

Citation Information

Patent Citations

  • An infrared shielding EVA photovoltaic film

    CN106590471B

  • Photovoltaic adhesive film with light conversion function

    CN220550130U

Cited By

  • Polyolefin elastomer for photovoltaic packaging film, preparation method and application

    CN121362278A

  • A polyolefin elastomer for photovoltaic encapsulation films, its preparation method and application

    CN121362278B